Sentence Types in Elle Magazine Fashion Articles - Nurul Aulia, Putri Nadzifah; Siti Yuliah; Febryanto, Mohammad (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
This study analyzed types of sentences used in five fashion articles from Elle Magazines. The data were taken purposively from different publications, which were from October 2023 until March 2024. The aims of this study were to analyze the use of sentence types and to identify the most used sentence types in Elle Magazines. This study applied Oshima & Houge’s theory to analyze types of sentences. The method used in this study was qualitative method since the data were in the form of texts. Simple calculation was used to identify the frequency of each type of sentence found. The process of analysis involved identifying the clauses to determine sentence types based on Oshima & Hogue’s theory. The findings showed that complex sentences are mostly used in the magazines, which had 45.7%, followed by simple sentences 28.6%, compound-complex sentences 17.1% and compound sentences 8.6%. The findings of this study may have significant implications both theoretically and practically. Theoretically, the findings can enhance grammar knowledge and provide English students’ chance to deepen their skill especially in creative writing. Practically, this study contributes editorial writers’ understanding of sentence types to make informed choices about how to successfully express their message to their target audience.